Does the Factor Structure of Military Sexual Stressors in Men Correspond to Women's? A Confirmatory Factor Analysis Using the Sexual Harassment Inventory. Issue 2 (1st February 2016) - Reddy, Madhavi K.; Murdoch, Maureen
ABSTRACT: Objectives: Unwanted sexual stressors experienced by military men and women are associated with a host of negative physical and mental health problems. Government officials are making it a priority to put a stop to these unwanted sexual experiences. However, the measure typically used measures sexual stressors much better for women than for men. The purpose of the present study was to test the factor structure of an alternative measure, the Sexual Harassment Inventory (SHI), to examine whether sexual stressors experienced by men correspond to women's experiences. Methods: We used three preexisting datasets in which the SHI was used to assess active and former military members' sexual stressor experiences. We conducted an exploratory factor analysis to identify women's response patterns and a confirmatory factor analysis to determine whether men's response patterns corresponded to women's. Results: Findings showed that the SHI has evidence of factorial validity in female service members and adequate, but not exceptional, factorial fit for male service members. Conclusions: It is imperative that more work be done to better understand how men experience and perceive potential military sexual stressors and how those perceptions and experiences compare to women's.